Rent, State and the Market: The Political Economy of the Transition to Self-sustained Capitalism (Distinguishedl Lecture) (The Pakistan Development Review, 1994)
In opposition to the now generalised critique of rent-seeking the following contribution establishes the inevitable character of the emergence of a rent problem in nearly any transition to capitalism from pre-capitalist relations of production. The only possibility of avoiding this possibility would be a rapid demographic decline or an equally rapid increase in availability of productive land. This rent problem in underdeveloped countries is aggravated by the existence of technically more advanced economies. Integration into the world economy can contribute to the management of this rent problem, but does not abolish it. The topic of development economics is, therefore, the combination of market regulation with non-market regulation in order to move the respective underdeveloped economy to a state where.rent can be abolished by the extension of the market mechanism. In contrast to the recommendations of the Bretton Woods Institution, the mere reinforcement of market regulation and the withdrawal of the state from economic regulation cannot be considered as sufficient for moving underdeveloped economies to self-sustained growth which allows market regulation.